2023
DOI: 10.3390/ijms24032431
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Uterine Leiomyoma from Women Exposed to Different Air Pollution Levels in Metropolitan Cities of Sao Paulo, Brazil

Abstract: Leiomyomas (LMs) are the most frequent uterine benign tumors, representing the leading cause of hysterectomy indications worldwide. They are highly associated with women’s reproductive complications, and endocrine disruptors may influence their etiology. In this sense, air pollution represents a relevant hormonal disruptor that acts on key signaling pathways, resulting in tumor development and infertility. Our goal was to evaluate submucosal LM samples from patients living in the metropolitan and Sao Paulo cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Surprisingly, AHR was significantly overexpressed in uterine and this overexpression was correlated with living in Tehran (capital of Iran), smoking, living near polycyclic aromatic hydrocarbon producing companies and eating grilled meat [219]. Air pollution represents a relevant hormonal disruptor that acts on key signaling pathways, resulting in tumor development and infertility [220]. UF Patients had significantly higher levels of total urinary mono-ethylhexyl phthalate (ΣMEHP), mono-n-butyl phthalate (MnBP), and monoethyl phthalate (MEP) [221].…”
Section: Avoiding Phthalate Exposurementioning
confidence: 99%
“…Surprisingly, AHR was significantly overexpressed in uterine and this overexpression was correlated with living in Tehran (capital of Iran), smoking, living near polycyclic aromatic hydrocarbon producing companies and eating grilled meat [219]. Air pollution represents a relevant hormonal disruptor that acts on key signaling pathways, resulting in tumor development and infertility [220]. UF Patients had significantly higher levels of total urinary mono-ethylhexyl phthalate (ΣMEHP), mono-n-butyl phthalate (MnBP), and monoethyl phthalate (MEP) [221].…”
Section: Avoiding Phthalate Exposurementioning
confidence: 99%
“…[1][2][3] In practice, it is only during recent years, the reproductive health impacts perturbed by air pollution become a hot research topic in environmental epidemiology. 4,5 The adversely reproductive health effects induced by air pollution can result in lower human fertility, [6][7][8][9] pregnancy loss, 10 preterm birth, 11 fetal growth restriction 12 and stillbirth. 13 Existing evidence regarding relationships between air pollutants exposure and infertility among couples who are attempting to conceive naturally has indicated that pre-gestational or gestational exposure to fine particulate matter (PM2.5) is associated with decreased fertility and increased pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%